Dynamical behaviour of fractional order tumor-immune model with targeted chemotherapy treatment - Kumar Gupta, Praveen; Dhar, Biplab (International Journal of Engineering and Technology, 2018)
In this study, we discussed the fractional order model of tumor-immune system based on Liuâ€˜s model. We examine the dynamic behaviour of tumor growth and investigate the conditions of tumor removal mathematically. We discussed qualitative analysis on the mathematical model and defined the existence and uniqueness conditions. Local stability is also checked for tumor-free equilibrium point. We give facts about that tumor growth rate, source rate of immune cells, and death rate of immune cells play vital role in tumor dynamics. Numerical simulations are demonstrated to reveal the analytical results.Â Â